(untitled) (Journal of the College of Education for Women, 2026)
The research aimed to identify the level of awareness of educational innovations in the field of teaching science among student teachers at the Faculty of Education, Sana’a University. The researchers adopted the descriptive survey approach, and a knowledge test was prepared in light of educational innovations. The research was applied to a sample of (92) student teachers specialized in (chemistry, physics, biology). The results of the research showed that the level of awareness of student teachers in educational innovations in the field of teaching science in general is very weak, and there are statistically significant differences between the average scores of males (30.04) and the average scores of females (36.24) in the degree of their awareness of educational innovations in the field of teaching sciences is in favor of females with the highest arithmetic mean. The results also showed that there are no statistically significant differences between the mean scores of student teachers in the degree of their awareness of educational innovations in the field of teaching science according to the specialization variable (chemistry, biology, physics).